2022
DOI: 10.1002/cmdc.202100727
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Structure‐Activity Relationship of Dihydromethysticin in Reducing Nicotine‐Derived Nitrosamine Ketone (NNK)‐Induced Lung DNA Damage against Lung Carcinogenesis in A/J Mice

Abstract: Lung cancer is the leading cause of cancer-related deaths and chemoprevention should be developed. We recently identified dihydromethysticin (DHM) as a promising candidate to prevent NNK-induced lung tumorigenesis. To probe its mechanisms and facilitate its future translation, we investigated the structureactivity relationship of DHM on NNK-induced DNA damage in A/J mice. Twenty DHM analogs were designed and synthesized. Their activity in reducing NNK-induced DNA damage in the target lung tissues was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The in vivo structure-activity relationship study found that the unnatural enantiomer of DHM was more potent than the natural enantiomer in NNK-induced A/J mice. More importantly, DHM analogues with high structural similarity show distinct efficacy in reducing NNK-induced DNA damage [ 61 ]. Moreover, it was determined that the methylenedioxy functional group in DHM that effectively reduced O 6 -mG adducts formation was critical to the chemopreventive activity and the lactone of DHM could be modified [ 61 , 62 ].…”
Section: Chemoprevention Of Lung Cancer By Dietary Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo structure-activity relationship study found that the unnatural enantiomer of DHM was more potent than the natural enantiomer in NNK-induced A/J mice. More importantly, DHM analogues with high structural similarity show distinct efficacy in reducing NNK-induced DNA damage [ 61 ]. Moreover, it was determined that the methylenedioxy functional group in DHM that effectively reduced O 6 -mG adducts formation was critical to the chemopreventive activity and the lactone of DHM could be modified [ 61 , 62 ].…”
Section: Chemoprevention Of Lung Cancer By Dietary Phytochemicalsmentioning
confidence: 99%
“…More importantly, DHM analogues with high structural similarity show distinct efficacy in reducing NNK-induced DNA damage [ 61 ]. Moreover, it was determined that the methylenedioxy functional group in DHM that effectively reduced O 6 -mG adducts formation was critical to the chemopreventive activity and the lactone of DHM could be modified [ 61 , 62 ]. It was also found that DHM decreased the level of O 6 -mG in female C57BL/6 mice.…”
Section: Chemoprevention Of Lung Cancer By Dietary Phytochemicalsmentioning
confidence: 99%